PTH-014 Post-polypectomy surveillance in the english bowel cancer screening programme: a prospective cohort study, preliminary results. (8th June 2018) - Bonnington, Stewart; Sharp, Linda; Rutter, Matt
Abstract : Introduction: The English Bowel Cancer Screening Programme (BCSP) offers individuals aged 60 to 74 years guaiac FOB testing (gFOBt), with an invitation for colonoscopy if positive. Of more than 3 00 000 individuals who have attended for colonoscopy, over 45 000 attended post-polypectomy surveillance (PPS) after having intermediate (IR) or high risk (HR) adenomas detected and resected at screening. It is established that screening reduces mortality from colorectal cancer (CRC). However, robust evidence to support PPS is lacking. Methods: Details were extracted from the BSCP database for individuals who attended PPS from the start of the BCSP in 2006 until 3/1/2017. Data were analysed using Stata 14. Results: 67, 435 PPS episodes were performed in 45 151 individuals. 60% of individuals had attended only 1 PPS episode, 34% attended 2, 5% attended 3, and 0.4% attended 4 or 5. PPS episodes per year greatly increased over the study period. In 2008, 453 episodes were attended, rising to 13 698 in 2016 (figure 1). 70% of those attending PPS were male. 44% were aged 60–64 at the time of index screening, 43% aged 65–69, and 10% aged 70–74. The oldest age group had a higher proportion (68%) of HR individuals than in the younger groups. Screening risk category varied with gender. Overall, 40% of females and 51% of males were HR (figure 2). Overall, the findings at first PPS demonstrate a high proportion of individuals with no further adenoma found (table 1). Conclusions: PPS accounts for an increasing proportion of endoscopy workload in the BCSP and more broadly in the UK and internationally. These results demonstrate a low proportion of CRC or IR or HR adenomas diagnosed at PPS in the BCSP. Individuals with HR adenomas at screening more often had further adenomas detected at first PPS when compared to those with IR adenomas at screening. HR individuals also had a higher probability of IR or HR adenomas at first PPS. CRC diagnosis at first PPS was low in both groups (≤0.5%). Further evaluation of the BCSP database is ongoing in order to identify subgroups most likely to benefit from PPS.